Improving Mathematics Achievement in the New Normal Education System Using Genyo E-Learning - Leadean Jay Capacio (International Journal of Theory and Application in Elementary and Secondary School Education, 2021)
Mathematics as a discipline effectively learned when teacher-assisted instruction is present has now aided with computer-assisted learning. This study assessed the effectiveness of Genyo-E-Learning in Online Distance Learning through a quasi-experimental pretest-posttest control group design. Pupils have matched accordingly with their Mathematics grades in the third-grading period. Pretest underwent KR20 and Levene’s Test of Homogeneity of Variance to see if the covariate is reliable and groups are at the same level. As shown in the Schema of Classes, the researcher designed two lesson outlines with different structures for the intact groups covering the topic: Circumference of a Circle. The lesson for the Control Group was delivered through the Conventional Virtual Lecture Method, while the Experimental Group had Genyo E-Learning as an aid for transmission. The post-test scores were the basis as to what group the significant difference favors. Post-tests were treated with ANCOVA at a 0.05 significance level. The researcher used the National Achievement Test Descriptive Equivalence Table to determine groups' mastery level and used the Evaluation Form on the Excerpts of Online Classes to evaluate the degree of pupils' interactivity toward the lesson. Mathematics Achievement of pupils taught with Genyo E-Learning is greater than that of Conventional Virtual Lecture Method teaching and rated Very Satisfactorily and Satisfactorily respectively based on Interactivity Evaluation. More pupils from the Experimental Group achieved Mastered Level based on the Achievement Level Scale. Genyo E-Learning Systems could improve Mathematics Achievement in the New Normal Education System.